Design of a Mobile-Based Wedding Information and Booking System using Backend as a Services (BaaS) on android platform - Mahirssa, Rafif; Fachrie, Muhammad (Universitas PGRI Semarang, 2024)
Nowadays, wedding organizer services have become a necessity in wedding events. However, it is often found that bookings are made manually to the vendor's location which results in impracticality. This research aims to build an application that brings practicality in the field of wedding organizers. Later this application has an online booking function carried out by wedding bookers and can establish communication with vendors in making wedding bookings. The focus of the research is to provide practicality to bookers and vendors. This research uses the Case Study method, interviews and observations conducted at Omah Kebon Resto as a case study. The application was built based on Android with Cloud Baas services on the Firebase platform for database management. The final evaluation was carried out by distributing questionnaires to respondents for the level of satisfaction of using the application built. The results stated that 37.12% of respondents were very positive, 45.41% stated positive, 13.54% stated neutral, and 3.93% stated negative. So, it can be concluded that respondents feel positive if this application can help practicality in getting information and booking wedding organizer vendors.